Concept of Language Politeness and Building Character Education - UMBAR, K. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This research is based on the increasingly numerous problems of character degradation in education, particularly the loss of language politeness, whether in verbal or written. This research is a qualitative study. In order to finish this research, the researcher used content analysis toward the verse stated in Al-Qur’an as the primary data source. The result of the research was that there are six language politeness principles in Al-Qur’an, namely qawlan sadida, qawlan ma’rufa, quwlan baligha, qawlan maysura, qawlan layyinan, and qawlan karima. There are 26 translatable maxims in those six principles. RESUMEN Esta investigación se basa en los problemas cada vez más numerosos de la degradación del carácter en la educación, particularmente la pérdida de cortesía del lenguaje, ya sea verbal o escrito. Esta investigación es un estudio cualitativo. Para finalizar esta investigación, el investigador utilizó el análisis de contenido hacia el verso declarado en Al-Qur’an como la fuente principal de datos. El resultado de la investigación fue que hay seis principios de cortesía lingüística en Al-Qur’an, a saber, qawlan sadida, qawlan ma’rufa, quwlan baligha, qawlan maysura, qawlan layyinan y qawlan karima. Hay 26 máximas traducibles en esos seis principios.